Mitochondrial genome of the acorn barnacle Tetraclita rufotincta Pilsbry, 1916: highly conserved gene order in Tetraclitidae - Jun Song; Xin Shen; Ka Hou Chu; Benny Kwok Kan Chan (Mitochondrial DNA. Part B. Resources, 2017)
The complete mitochondrial genome of the intertidal barnacle Tetraclita rufotincta Pilsbry, 1916 (Crustacea: Maxillopoda: Sessilia) is presented. The genome is a circular molecule of 15,236 bp, which encodes a set of 37 typical metazoan mitochondrial genes. All non-coding regions are 438 bp in length, with the longest one speculated as the control region (242 bp), which is located between srRNA and trnK. Comparison of the genome and those of three other species from Tetraclitidae shows that gene arrangement is identical, indicating that the mitochondrial gene order is highly conserved in the family. Moreover, in comparison with the pancrustacean ground pattern, the four species of Tetraclitidae share three large conserved gene blocks. Phylogenetic analysis based on 13 mitochondrial PCGs shows that Chelonbia testudinaria (Coronulidae) clusters with the four species of Tetraclitidae. Within Tetraclitidae, T. serrata clusters with T. japonica, and the two grouped with T. rufotincta with high support (BP = 100), with T. divisa as the most distantly related species (BP = 100).